Synthesis of Benzothiophenones and Naphthothiophenone as Anticholinesterases - Jung, D.I. (Asian Journal of Chemistry, 2013)
Since AChE and BuChE belong to the same serine hydrolazes, we designed and synthesized compounds 1-6 as anticholinesterases and measured their inhibition poteucies on ChEs. 7-Methoxy-3H-benzo[c]thiophen-1-one 4, 4,6-dibromo-5,7-methoxy-3H-benzo[c]thiophe-1-one 5 and 9-methoxy-3H-naphtho-[2,3-c]thiophen-1-one 6 were synthesized by using ethyl 2-methoxy-6-methylbenzoate, ethyl 3,4-dibromo-2,4-dimethoxy-6-methylbenzoate and ethyl 1-methoxy-3-methyl-2-naphthoate.